2019
DOI: 10.1093/mnras/stz3067
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of FR I interaction with a hot X-ray bridge in the A2384 galaxy cluster

Abstract: Clusters of varying mass ratios can merge and the process significantly disturbs the cluster environments and alters their global properties. Active radio galaxies are another phenomenon that can also affect cluster environments. Radio jets can interact with the intra-cluster medium (ICM) and locally affect its properties. Abell 2384 (hereafter A2384) is a unique system that has a dense, hot X-ray filament or bridge connecting the two unequal mass clusters A2384(N) and A2384(S). The analysis of its morphology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
(88 reference statements)
2
6
0
Order By: Relevance
“…We then obtained its GMRT 325 MHz data to study the radio environment around the cluster. We found a Fanaroff-Riley Class I (FR I henceforth) (Fanaroff & Riley 1974) radio galaxy, a member of this cluster whose northern radio lobe pushes and distorts the X-ray filament eastwards (Parekh et al 2019). Such a displacement in the X-ray filament by the radio lobe is observed here for the first time on such a large scale.…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations
“…We then obtained its GMRT 325 MHz data to study the radio environment around the cluster. We found a Fanaroff-Riley Class I (FR I henceforth) (Fanaroff & Riley 1974) radio galaxy, a member of this cluster whose northern radio lobe pushes and distorts the X-ray filament eastwards (Parekh et al 2019). Such a displacement in the X-ray filament by the radio lobe is observed here for the first time on such a large scale.…”
Section: Introductionsupporting
confidence: 49%
“…A total of 56 cluster member galaxies have been identified, and both the X-ray gas and galaxy distributions approximately define the same bimodal structure (Maurogordato et al 2011). In a previous work (Parekh et al 2019), it was observed that, in the Chandra X-ray map, there is a bend visible in the X-ray bridge ∼ 800 kpc from the X-ray peak of A2384(N). We then obtained its GMRT 325 MHz data to study the radio environment around the cluster.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…According to our expectations from detailed simulations, the best places to search for LSS activity such as infalling substructures and the hot dense fraction of the WHIM is close to nearby galaxy clusters, in their outskirts, and in the presumed warm filaments connecting them. Therefore, searching in the direction of superclusters, between galaxy clusters, or within large-scale galaxy structures or galaxy pairs using X-ray and and Sunyaev-Zeldovich (SZ) observations seems to be the currently most promising way forward (e.g., Fujita et al 2008;Werner et al 2008;Fang et al 2010;Dietrich et al 2012;Planck Collaboration et al 2013;Nevalainen et al 2015;Eckert et al 2015;Bulbul et al 2016;Parekh et al 2017;Akamatsu et al 2017;Alvarez et al 2018;Tanimura et al 2019;de Graaff et al 2019;Parekh et al 2020;Tanimura et al 2020;Ghirardini et al, subm.). (Jarrett et al 2000).…”
Section: Introductionmentioning
confidence: 99%